Effects of swimming in cold water on lipolysis indicators via fibroblast growth factor-21 in male Wistar rats - Sara Shams; Mostafa Tavasolian; Sadegh Amani-Shalamzari; Pezhman Motamedi; Hamid Rajabi; Katja Weiss; Beat Knechtle (Biochemistry and Biophysics Reports, 2024)
This study aimed to investigate the effects of swimming in cold water on the release of FGF21 from various tissues and its impact on fat metabolism. Twenty Wistar rats were randomly divided into three groups: untrained (C), trained in thermo-neutral water (TN, 30 °C) and trained in cold water (TC, 15 °C). The training groups swam intervals (2–3 min) until exhaustion, 1 min rest, three days a week for six weeks, with 3–6% bodyweight load. The mRNA expression of variables was determined in white fat tissue (WAT), and FGF21 protein was also measured in the liver, brown fat tissue (BAT), serum, and muscle. The experimental protocols resulted in lower body weight gain, associated with reduced WAT volume; the most remarkable improvement was observed in the TC group. Swimming significantly increased FGF21 protein levels in WAT, BAT, and muscle tissues compared to the C group; substantial increases were in the TC group. Changes in FGF21 were highly correlated with the activation of genes involved in fat metabolisms, such as CPT1, CD36, and HSL, and with glycerol in WAT. The findings indicate a positive correlation between swimming in cold water and the activation of genes involved in fat metabolism, possibly through FGF21 production, which was highly correlated with fat-burning genes.